Fictions of youth: childness in selected West African novels, 1991-2009 - Moellenberg, T (2015)
This thesis examines child figures in Anglophone West African novels by Ben Okri, Chris Abani, Uzodinma Iweala, Delia Jarrett-Macauley, Helen Oyeyemi, and Yaba Badoe. A "child" here is defined as a human person under age 18 and is referred to using the term childness, drawing from the work of children's literature scholar Peter Hollindale. The thesis begins by reviewing some of the ways literary scholars have discussed images of childness in West African novels to date, exploring common themes such as "Empire," "nationhood" and "identity." The next three chapters, then, seek to move beyond some of these established readings. Chapter 1 investigates Ben Okri's "Azaro" in The Famished Road (1991) as a means of exploring aspects of the artist's creative life. Okri’s child figure, I propose, shares much in common with the "artist" from his earlier fictions, Flowers and Shadows (1980) and The Landscapes Within (1981). Chapter 2, similarly, considers the way in which child figures have a versatile function in Chris Abani’s Song for Night (2007), Uzodinma Iweala's Beasts of No Nation (2005), and Delia Jarrett-Macauley's Moses, Citizen and Me (2005), propping up an implicit argument in favor of humanitarian intervention in civil war. Yet here the thesis also considers some of the downsides to children’s instrumentalization: Jarrett-Macauley and Iweala depersonalize the child figure in their fictions, I argue. The child is drained of a convincing sense of an individuality and agency of his or her own. Chapter 3 continues to explore the figure of the child as a complex and multivalent symbol. However, it finds that Helen Oyeyemi's The Icarus Girl (2005) and Yaba Badoe's True Murder (2009) do not disavow children's personhood, as Iweala and Jarrett-Macauley appear to do. Rather, the "otherness" of children, which is explored in their novels alongside the alterity of black persons, cultural minorities, and women, helps to draw attention to the agency of children. That is to say, Oyeyemi and Badoe show us children as subversive, contributing their own social meanings to the category of "youth," even whilst they are passively constructed or "othered" by adults in the novels. As an additional concern, the thesis also examines how authors have recourse to western conceptions of childness, not only to the traditions of their native countries, as we might as expect. The goal throughout is to highlight the child as a multifunctional figure, while also bringing attention to several specific ways in which African child figures function, including as a means of exploring human creativity, of arguing implicitly for more humanitarian involvement in African civil wars, and of establishing the full extent of the migrant's "outsiderness" in the space(s) of diaspora.